The storyteller - Turk, Evan (New York : Atheneum Books for Young Readers, 2016)
In a time of drought in the Kingdom of Morocco, a storyteller and a boy weave a tale to thwart a Djinn and his sandstorm from destroying their city.
Map on endpaper.
School Library Journal starred, May 2016
Booklist starred, June 2016
Pub Weekly, April 2016
Kirkus Starred, April 2016
Horn Book, October 2016
Keywords: Storytelling -- Fiction; Droughts -- Fiction; Genies -- Fiction; Morocco -- Fiction